Temporal contrast enhancement of energetic laser pulses by filtered self-phase-modulation-broadened spectra - Buldt, Joachim; Mueller, Michael; Klas, Robert; Eidam, Tino; Limpert, Jens; Tuennermann, Andreas (Optics Letters, 2017)
We present a novel approach for temporal contrast enhancement of energetic laser pulses by filtered self-phase-modulation-broadened spectra. A measured temporal contrast enhancement by at least seven orders of magnitude in a simple setup has been achieved. This technique is applicable to a wide range of laser parameters and poses a highly efficient alternative to existing contrast-enhancement methods.
CRIS-Team Scopus Importer:2023-04-20